To Evaluate the Level of Serum Cholesterol, Uric Acid, Urea, Creatinine and Urine Albumin in Diabetic Patients from Peshawar - Rabia Mehreen, Falak Niaz, Aziz Ur Rehman, Syed Jawad Ali Shah, Muhammad Fayaz, Faisal Khan, Abdullah, Muhammad Amad Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes Mellitus is a metabolic disorder that causes chronic hyperglycemia. Its progression may lead to the dysfunction of multiple organs such as kidneys, eyes, blood vessels and neurons. It is caused by a combination of two basic factors that are abnormal insulin secretion and sensitivity of tissues to insulin. Group of parameters were selected in this study that have some relation with diabetes mellitus which included serum uric acid, cholesterol, urea, creatinine and urine albumin. The aim of this study was to find the impact of diabetes mellitus on these parameters. The blood and urine samples were collected according to the recommended protocol. The biochemical parameters had been determined by Micro-lab 300 biochemistry analyzer and urine qualitative was performed through uric-v3 strips. A cross-sectional study was carried out by 105 diabetic subjects and their samples were collected from different laboratories of district Peshawar. The mean age was 44 ± 12.54 years and samples were comprised of 50.48%male and 49.52% females. According to our findings among 105 diabetic patients 29% had elevated uric acid, 69% cholesterol, 57% urea, 39%creatinine and 40% urine albumin levels respectively. The overall result concluded that these parameters must be considered or taken seriously to monitor and to limit its progression to irreversible changes. Keywords: cholesterol, creatinine, diabetes mellitus, nephropathy, serum urea, uric acid, urine albumin.